TPS-3R Program Strategy in Bandar Lampung City - Anis Septiana; Pitojo Budiono; Feni Roslia (PERSPEKTIF, 2022)
Waste production in Bandar Lampung City reaches 4000 tons per day. Heaps of waste that do not decompose become problems such as plastic waste, food waste, and paper materials. The City Government of Bandar Lampung made Regional Regulation Number 05 of 2015 concerning Waste Management in the City of Bandar Lampung by implementing:waste management through TPS 3R. The TPS 3R concept is a place for collecting, sorting, reusing, recycling, and processing regional scale activities. The area of TPS 3R, larger than 200 m2, is equipped with a sorting room, organic waste composting, warehouse, buffer zone and does not interfere with aesthetics and traffic. This research leads to the development of waste processing facilities using a Cost Benefit Analysis approach with a plan for two scenarios, namely Scenario A (business-as-usual) and Scenario B (waste processing using TPS-3R. The pattern of waste management in Bandar Lampung City uses the direct collection method (door to door) and immediately accommodated in Bakung TPA A strategy to optimize waste management at 3R TPS through outreach to the public.